A simulation framework for reciprocal recurrent selection-based hybrid breeding under transparent and opaque simulators - Zhang, Zerui; Wang, Lizhi (Frontiers in Plant Science, 2023)
We present a modular simulation framework for reciprocal recur- rent selection based hybrid breeding. Consisting of multiple modules such as heterotic separation, genomic prediction, and genomic selection, this simulation framework allows breeders to efficiently simulate the hybrid breeding process with multiple options of simulators and decision-making strategies. We also integrate the recently proposed concepts of transparent and opaque simulators into the framework in order to reflect the breeding process more realistically. As such, this framework enables breeders and researchers to evaluate the effectiveness of competing decision-making strategies.